FAKTOR - FAKTOR YANG MEMPENGARUHI BIAYA UTANG PADA PERUSAHAAN DALAM KOMPAS 100 - Septian, Muhamad; Panggabean, Rosinta Ria (Jurnal Ekonomi, 2017)
This study aims to determine the effect of Good Corporate Governance (GCG) which is proxied through: the proportion of independent commissioners, managerial ownership, institutional ownership, quality audits, and family ownership on the cost of debt. The objects of this study are companies listed in Compass 100 period August 2013 January 2014. The method used to take samples of the study using purposive sampling method. Data analysis methods used are descriptive statistics, the classical assumption test, and hypotheses test. Based on the results of hypothesis testing that performed by using multiple regression analysis at the 0.05 significant level, the results of this study prove that the proportion of independent commissioners has a significant negative effect on the cost of debt. Managerial ownership has a positive significant effect on the cost of debt. Institutional ownership, quality audits, and family ownership has no significant effect the cost of debt.